New Structures in the Basidiomycete, Coniophora cerebella - Langvad, Finn (1971)
Previously undescribed structures found in Coniophora cerebella are described. They appear like spherical bodies, about 0.5 μm in diameter, situated along the wall and septa of the hyphae. They are not membrane bound and seem to be composed of ribosomes.